PERUBAHAN LANSKAP DI KOTA BANJARBARU DARI 1999 SAMPAI 2011 - Suryanullah, Ahmad Sholehuddin (Handep: Jurnal Sejarah dan Budaya, 2024)
This article discusses the process of landscape change and its impact in Banjarbaru City from 1999 to 2011. Since officially becoming a municipality in 1999, the Banjarbaru City Government has enacted a range of urban planning policies that have successfully attracted investment in the industrial and housing sectors. This influences the growth of the population and the landscape condition of Banjarbaru City. This article applied historical methods using sources such as newspapers, maps, reports from the Central Statistics Agency (BPS), and government policy letters. This research indicates that Regional Regulation Number 05 of 2001, which focuses on urban spatial planning, garnered positive interest from investors in the industrial and housing sectors during 2003 and 2004. In addition, Rudy Ariffin’s plan to relocate the capital of South Kalimantan Province was included in the 2006-2010 Regional Medium Term Development Plan (RPJMD). These initiatives resulted in significant changes to the landscape, transforming green spaces into residential and industrial areas. Local communities and mining companies further intensified these alterations through traditional and modern diamond mining activities. The ongoing process of landscape transformation paralleled a population increase from 2008 to 2011, with green land transformed into urbanised areas from 2005-2011. This article seeks to bridge a gap in environmental historiography in Indonesia by examining the phenomenon of landscape change as a significant event in environmental history